(untitled) (Experimental biology, 2016)
In territory of Kazakhstan, many plants grow in saline soils, which is not very favorable for them. Today this situation has become an actual problem. The article presents the results of studies on the processing seed varieties of spring wheat cytokinin mediators, which increases the growth of seeds and resistance to salt stress. The main objective was investigation of the new growth-bioregulator of agricultural plants, positively effect on fertility and resistance to stressful factors of plants. It is known that, the bioregulator of cytokinin mediator in very small concentration influences growth and development, and also the adaptation of plants to environmental conditions. Therefore application of cytokinin mediator as the accelerator of growth and increase of resistance to stressful factors of plants is very advantageous and economic effective. The studies revealed that the most optimal concentration of cytokinin mediators for varieties of spring wheat is 100 ng / ml.